OBJECTIVES OF THE IMPLEMENTATION IN THE REPUBLIC OF ARMENIA OF THE RIGHT TO HOUSING FOR CHILDREN LEFT WITHOUT PARENTAL CARE, WHO ARE UNDER GUARDIANSHIP AND IN A FOSTER FAMILY - Petrosyan, Rubina (State and Law, 2021)
The provision of living quarters that meet the requirements of the law for children left without parental care, who are under guardianship, guardianship and in a foster family, is necessary to ensure the physical, mental, spiritual, moral and social development of the child, as well as to ensure the right of children to the required standard of living. Meanwhile, according to the legislation of the Republic of Armenia, based on the chosen form of child care and upbringing, a discriminatory approach is enshrined in the implementation of the right of children with the same status to receive housing, which is not based on the fundamental principle of the family code - ensuring the “best interests of the child”, but also inconsistent with the constitutional prohibition of discrimination.